2016
DOI: 10.3390/ijerph13111106
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Pollution, Meteorological Factors and Outpatient Visits for Eczema in Shanghai, China: A Time-Series Analysis

Abstract: Environmental irritants are important risk factors for skin diseases, but little is known about the influence of environmental factors on eczema incidence. In this time-series study, our objective was to examine the associations of environmental factors with outpatient visits for eczema. Daily outpatient visits between 2007 and 2011 (1826 days) were collected from Huashan Hospital in Shanghai, China. We used an overdispersed generalized additive model to investigate the short-term association between environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 47 publications
7
71
2
Order By: Relevance
“…Acute effects of air pollution on AD were also found in previous studies. A similar study in Shanghai, China also found the strongest effects between air pollutants and outpatient visits for eczema at lag0 . A panel study in Korea found an increase in PM 10 and NO 2 by 10 units increased the risk of eczema symptoms on the same day by 3.2% (95% CI: 1.5%, 4.9%) and 5.0% (95% CI: 1.4%, 8.8%), respectively .…”
Section: Discussionmentioning
confidence: 75%
“…Acute effects of air pollution on AD were also found in previous studies. A similar study in Shanghai, China also found the strongest effects between air pollutants and outpatient visits for eczema at lag0 . A panel study in Korea found an increase in PM 10 and NO 2 by 10 units increased the risk of eczema symptoms on the same day by 3.2% (95% CI: 1.5%, 4.9%) and 5.0% (95% CI: 1.4%, 8.8%), respectively .…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, patients would sweat more in warm seasons, and this might directly irritate the skin lesions of eczema combining with air pollutants. 10 However, our study results still apply to a growing number of people suffering from eczema and throw lights on relationships between environmental factors and eczema. 8,10,41,47 The univariate analysis and multivariate analysis of overall effects showed different effects of environmental factors on male and female outpatients with eczema.…”
Section: Discussionmentioning
confidence: 78%
“…10 On the contrary, the daily eczema outpatients were significantly negatively associated with relative humidity, which indicated relative humidity might play a protective role in eczema. 10 On the contrary, the daily eczema outpatients were significantly negatively associated with relative humidity, which indicated relative humidity might play a protective role in eczema.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations